"A Huge, Hidden Problem": Australian Health Practitioners' Views and Understandings of Reproductive Coercion. (August 2019) - Tarzia, Laura; Wellington, Molly; Marino, Jennifer; Hegarty, Kelsey
Reproductive coercion is understood as behavior interfering with a woman's reproductive autonomy. It is usually perpetrated by a male partner, and sometimes by other family members. Reproductive coercion encompasses violence, threats, or coercion to force a woman to become or remain pregnant, or to terminate a pregnancy. To date, few studies have focused on this topic, particularly using qualitative methods. In this article, we aim to explore how Australian health practitioners understand and perceive reproductive coercion. We conducted semistructured interviews with health practitioners from an Australian public hospital, and the resulting data were analyzed thematically. Overall, reproductive coercion was described as complex and hidden . There were diverse understandings around its parameters and scope, which were shaped by the participants' disciplines and paradigms. Our findings point toward a need for greater clarity around reproductive coercion and how it sits within a broader framework of violence against women, to facilitate cross-disciplinary collaborative responses.